Polymeric resins containing modified starch as environmentally friendly adsorbents for dyes and metal ions removal from wastewater - Wołowicz, Anna; Wawrzkiewicz, Monika; Podkościelna, Beata; Tarasiuk, Bogdan; Blazhevska Gilev, Jadranka; Sevastyanova, Olena (Frontiers in Chemistry, 2024)
New adsorbents have been developed in the form of polymer microspheres based on ethylene glycol dimethacrylate (EGDMA) and vinyl acetate (VA) (EGDMA/VA) containing starch (St) modified with boric acid (B) and dodecyl-S-thiuronium dodecylthioacetate (DiTDTA) for the removal of dyes: C.I. Basic Blue 3 (BB3) and C.I. Acid Green 16 (AG16) and heavy metal ions: Cu(II), Ni(II), and Zn(II) ions from water and wastewater. The adsorbents were characterized by ATR/FT-IR, DSC, SEM, BET, EDS and pHPZC methods. These analyses demonstrated the successful modification of microspheres and the increased thermal resistance resulting from the addition of the modified starch. The pHPZC for EGDMA/VA was 7.75, and this value decreased with the addition of modified starch (6.62 for EGDMA/VA-St/B and 5.42 for EGDMA/VA-St/DiTDTA). The largest specific surface areas (SBET) were observed for the EGDMA-VA (207 m2/g), and SBET value decreases with the modified starch addition (184 and 169 m2/g). The total pore volumes (Vtot) were found to be in the range from 0.227 to 0.233 cm3/g. These materials can be classified as mesoporous, with an average pore diameter (W) of 55 Å (5.35-6.10 nm). The SEM and EDS analyses indicated that the EGDMA/VA microspheres are globular in shape with well-defined edges and contain 73.06% of carbon and 26.94% of oxygen. The microspheres containing modified starch exhibited a loss of smoothness with more irregular shape. The adsorption efficiency of dye and M(II) ions depends on the phases contact time, initial adsorbate concentration, temperature, and the presence of competing electrolytes and surfactants. The equilibrium data were better fitted by the Freundlich isotherm model than by the Langmuir, Temkin, and Dubinin-Radushkevich models. The highest experimental adsorption capacities were observed for the BB3 dye which were equal to 193 mg/g, 190 mg/g, and 194 mg/g for EGDMA/VA, EGDMA/VA-St/B, EGDMA/VA-St/DiTDTA, respectively. The dyes and heavy metal ions were removed very rapidly and the time required to reach system equilibrium was below 20 min for M(II), 40 min for BB3, and 120 min for AG16. 50% v/v methanol and its mixture with 1 M HCl and NaCl for dyes and 1 M HCl for M(II) desorbed these impurities efficiently.